Habits and oral hygiene status of indigenous people with disabilities from the Misak community, Colombia - Herney Alonso Rengifo-Reina; Cinthya Solórzano-Vera; Ángela Liliana Grandas-Ramírez (Universidad de Antioquia, 2019)
Introduction: nearly 15% of the world's population lives with some kind of disability. Colombia has no official reports on indigenous people with disabilities. Being an indigenous person with a disability increases health vulnerabilities and the risk for oral diseases. The objective of this study was to describe the habits and oral hygiene status of people with disabilities living in the Misak (Guambiano) indigenous reserve in Silvia, Department of Cauca (Colombia), in 2016. Methods: a descriptive observational cross-sectional study was conducted. The entire population with some degree of disability in the Misak indigenous community was included, assessing their oral hygiene through Community Plaque Index (CPI) and collecting socio-demographic and oral health habits variables using descriptive analysis to correlate disability type with health habits and plaque index. Results: 46 people with some degree of disability were identified. Of these, 45.7% were women and aged 22.6 years in average. Cognitive disability was the most common, (54.3%). The study showed that 43.4% of people with disabilities brush their teeth at least once a day, with 44% needing help to do so. A bacterial plaque index of 91.8% was found. Conclusion: people with disabilities in the Misak indigenous community have a high community plaque index, which is considered a poor level, with inadequate oral hygiene habits.